Developing Tests and Questionnaires for a National Assessment of Educational Achievement - Anderson, Prue (Washington, DC : World Bank, 2012)
Developing tests and questionnaires for a national assessment of educational achievement addresses the design of two types of data collection instruments: student achievement tests and background questionnaires. Part one covers the development of an assessment framework and a test blueprint, item writing, pre testing, and final test layout. Part two delineates comparable stages and activities in the construction of background questionnaires, which are used to gather information from students, teachers, head teachers, or parents on variables that might help explain differences in student performance on the achievement test. Part three describes how to design a manual for test administration to help ensure that all students take the test under standardized conditions. The compact disc (CD) that accompanies this book offered examples of well-designed test items, questionnaire items, and administration manuals drawn from national and international assessments and is meant to showcase the variety of ways in which assessment teams have approached the design of these instruments.